In-vivo antiparasitic assessment of garlic (Allium sativum) in Trypanosoma evansi-induced mice - Baba, Mohd Shukri; Abdul Izam, Muhammad Khairil Nizam (2017)
The resistance of antiparasitic drugs against zoonotic trypanosomiasis or Surra disease demanded the alternative treatment towards both infected human and animals as the priority focused nowadays. In this study, antiparasitic effects of Allium sativum (garlic) aqueous extract was compared with anti-trypanosomal drug berenil, on the growth and survival of the haemoflagellate Trypanosoma evansi in mice. Groups of male ICR strain mice aged 6 – 8 weeks with 20 – 25g body weight were infected with the parasite (5.0 × 103 T. evansi per mouse) and orally given pre-, concurrent- or post-infection treatments with A. sativum (0.1 mL of 15 µg/mL A. sativum per mouse). Stained blood slides were microscopically examined for the evaluation of selected parameters. The mice in negative control group succumbed to the T. evansi infections with rapid increase of parasitaemias. The survival time for the mice in pre-infection treatment groups was longer (96.58 ± 0.2 days) than those of the mice in the groups receiving concurrently or post-infection treatments. There was also a positive relationship (p ≤ 0.05, n = 6) between the mice survival time and the ability to inhibit the parasites growth in this group. The morphological changes of T. evansi cells were observed where the undulating membrane was destroyed and the cell became crescent-shaped. Finally, both of the posterior and anterior ends were tapered before the flagellum destroyed and disintegrated in which lead to death of the cells. The results from this study suggest that A. sativum has a stronger anti-parasitic activity against T. evansi by causing the destruction of the cells